Evaluation of occupational health checks for hospital employees. Issue 4 (4th November 2014) - Blake, Holly; Bennett, Eleanor; E. Batt, Mark
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to ascertain which employees choose to access occupational health checks (OHCs), their perceptions of the usefulness of information received and whether they choose to act on tailored advice provided. Design/methodology/approach – In total, 253 hospital employees attended workplace OHC then completed online questionnaire survey. Findings – Participants included new cases (80 per cent) and those who had accessed the service previously (20 per cent), all age categories (23-69 years) and all occupational groups, although the vast majority were in office-based sedentary job roles, nursing or allied health professions (AHP) (78.3 per cent). Almost half were overweight or obese (46.7 per cent); many reported existing health problems or family history of chronic disease. Participants perceived OHC s to be convenient, informative and useful for raising their awareness of health issues, reassurance and monitoring, early identification of potential health problems and signposting to appropriate services. Participants reported post-check dietary changes (41 per cent) and increases in physical activity (30 per cent); smokers reported quitting or cutting down (44 per cent) and those exceeding alcohol limits reported cutting frequency or units of consumption (48 per cent). More than half those advised to visit their GP complied (53 per cent). Research limitations/implications – Future studies should investigate the efficacy of OHCs and whether reported lifestyle changes are sustained in the long-term. Originality/value – General health checks can be feasibly delivered in a multi-site hospital workplace setting with diverse appeal. Provision of tailored health information can help to raise health awareness and motivate health behaviour change or maintenance amongst hospital employees, including those reporting risk factors for chronic disease. Employees value the investment of healthcare organisations in the health and wellbeing of their workforce.